1997
DOI: 10.1002/hlca.19970800510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysubstituted Pyrrolizidines from Proline Derivatives and Conjugated Nitroolefins

Abstract: Dedicated with best wishes to Professor Dieter Seebach on the occasion of his 60th birthday (12.11.97) The stereochemistry of 1,3-dipolar cycloaddition of azomethine ylides derived from aromatic aldehydes and L-proline alkyl esters with several nitroolefins was investigated. Cyclic and acyclic nitroolefins add to the Cmti form of the yhde in a highly diastereoselective but poorly regioselective manner to give pyrrolizidine derivatives. In a few cases, the stereochemical results strongly support a stepwise m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…The reaction between L-proline alkyl esters 135 and aromatic aldehydes 2 generated the azomethine ylides 136, which were trapped by a second aldehyde molecule to give mostly mixtures of the oxapyrrolizidines 137a, 137b and 138 (Scheme 34, Table 19). The oxapyrrolizidines were prone to cycloreversion to regenerate azomethine ylides 136, and in the presence of a range of conjugated nitroolefins underwent cycloaddition to afford the corresponding pyrrolizidines [111]. A number of reactions of N-alkylated glycine ethyl esters and paraformaldehyde have also been reported, which were conducted neat and under microwave irradiation, to afford the corresponding oxazolidines in moderate The reaction between L-proline alkyl esters 135 and aromatic aldehydes 2 generated the azomethine ylides 136, which were trapped by a second aldehyde molecule to give mostly mixtures of the oxapyrrolizidines 137a, 137b and 138 (Scheme 34, Table 19).…”
Section: Reactions Of Ylides From the Condensation Of Secondary Alphamentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction between L-proline alkyl esters 135 and aromatic aldehydes 2 generated the azomethine ylides 136, which were trapped by a second aldehyde molecule to give mostly mixtures of the oxapyrrolizidines 137a, 137b and 138 (Scheme 34, Table 19). The oxapyrrolizidines were prone to cycloreversion to regenerate azomethine ylides 136, and in the presence of a range of conjugated nitroolefins underwent cycloaddition to afford the corresponding pyrrolizidines [111]. A number of reactions of N-alkylated glycine ethyl esters and paraformaldehyde have also been reported, which were conducted neat and under microwave irradiation, to afford the corresponding oxazolidines in moderate The reaction between L-proline alkyl esters 135 and aromatic aldehydes 2 generated the azomethine ylides 136, which were trapped by a second aldehyde molecule to give mostly mixtures of the oxapyrrolizidines 137a, 137b and 138 (Scheme 34, Table 19).…”
Section: Reactions Of Ylides From the Condensation Of Secondary Alphamentioning
confidence: 99%
“…A number of reactions of N-alkylated glycine ethyl esters and paraformaldehyde have also been reported, which were conducted neat and under microwave irradiation, to afford the corresponding oxazolidines in moderate The reaction between L-proline alkyl esters 135 and aromatic aldehydes 2 generated the azomethine ylides 136, which were trapped by a second aldehyde molecule to give mostly mixtures of the oxapyrrolizidines 137a, 137b and 138 (Scheme 34, Table 19). The oxapyrrolizidines were prone to cycloreversion to regenerate azomethine ylides 136, and in the presence of a range of conjugated nitroolefins underwent cycloaddition to afford the corresponding pyrrolizidines [111]. A number of reactions of N-alkylated glycine ethyl esters and paraformaldehyde have also been reported, which were conducted neat and under microwave irradiation, to afford the corresponding oxazolidines in moderate yield [112].…”
Section: Reactions Of Ylides From the Condensation Of Secondary Alphamentioning
confidence: 99%
“…Five-membered cyclic azomethine ylides have been amply reported in pyrrolidine syntheses. Actually, a wide variety of procedures have been exploited for their generation: i) base-promoted elimination from N-(phenylthiomethyl)proline esters, 105 ii) reaction of proline with carbonyl compounds and concomitant decarboxylation, [107][108][109] iii) base-promoted elimination from N-methylpyrrolidine N-oxides, 110 iv) 1,4-prototropy of Nstyrilproline esters, 111 v) ring opening of 2,3-trimethyleneoxazole derivatives, 112,113 vi) desilylation of N-(trimethylsilyl)methyl-1-pyrrolinium salts, [114][115][116][117][118] and vii) deprotonation of N-(β-trifluoroethylidene)pyrrolidinium triflates. 119 As significative examples, the concise syntheses of the racemic pyrrolizidines 27 111 and 28 119 are outlined in Scheme 17, while Scheme 18 deals with the synthetic approach to racemic retronecine 29 reported by Vedejs and co-workers.…”
Section: Scheme 16mentioning
confidence: 99%
“…Of the different strategies to synthesise the oxazolidine ring-system, 1,3-dipolar cycloaddition is a leading technique [26][27][28][29][30]. In the present work, an interesting route utilising 1,3-dipolar cycloaddition has been used to synthesise oxazolidines [31][32][33][34]. The mechanism consists of the formation of the azomethine ylide in situ, followed by cycloaddition.…”
Section: Introductionmentioning
confidence: 98%
“…Our longstanding interest in 1,3-dipolar cycloaddition [41][42][43][44][45] led us to turn our attention on the direct synthesis of oxazolidine moieties by cycloaddition of non-stabilised azomethine ylides with carbonyl compounds. Orsini et al [32] and Felluga et al [33] had reported direct cycloaddition of azomethine ylides with carbonyl compounds. In the present work we have extensively studied reactions with aryl aldehyde as carbonyl compound to generate new stereocenters in the cycloadduct(s).…”
Section: Introductionmentioning
confidence: 98%